Perbandingan Tingkat Getaran dan Bunyi Pada Mesin Kapal Berdasarkan Jenis sistem - PAWANA, FAUZAN YAZI (Blueprint Journal, 2025)
This study explores how different types of damping systems affect vibration and noise levels in ship engines. The main goal is to assess the effectiveness of each damping system in reducing vibrations and noise, and to determine which system performs best in improving comfort and reliability. The approach combines direct experiments and literature review. Three damping types were tested: passive elastomer dampers, semi-active magnetorheological (MR) dampers, and fully active systems controlled by sensors and actuators. Results show that active systems are the most effective in reducing both low- and mid-frequency vibrations and noise. MR dampers perform well under variable load conditions, while passive systems are suitable for more stable operations. These findings offer a practical reference for selecting the right damping system tailored to a ship's operational needs.